'"Dochum glorie De agus onora na hEireann": Revising history in Ireland' - Limond, David (Palgrave, 2020)
This chapter discusses the details of the widely proposed “downgrading” of history in the Irish school curriculum.
The Palgrave Handbook of History and Social Studies Education
PUBLISHED
New York/London
Keywords: Education, Ireland; Curriculum reform, Ireland; History teaching, Ireland; EDUCATION; Educational Reform; Irish History; Children; Education; History